Komparasi Karakteristik Morfologi Sapi Simmental (Simmental Fleckvieh) dan Sapi Perah (Friesian Holstein) di Kabupaten Tulungagung - Alvina Nur Ramadhani; Anisaul Zahro; Dewi Rohmatul Ummah; Farah Hamidah; Luthfina Dwi Nastiti Damayanti; Yanuar Fauzanin; Desi Kartikasari (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2026)
This study aims to compare the morphological characteristics of Simmental Fleckvieh (Simmental) cattle and Friesian Holstein (FH) dairy cattle in Tulungagung Regency. The research was conducted in April–May 2026 at Lembu Mustika farm in Boyolangu District and Kradinan farm in Pagerwojo District. Preliminary observations and interviews were carried out to determine the morphological characters observed during the study. The research employed a descriptive qualitative approach through direct observation and structured interviews with farm owners and farm workers. The morphological characters observed included body size, body shape, body color, horn shape, hump presence, udder characteristics, and other physically visible traits. The data obtained were analyzed descriptively by comparing the morph ological characteristics of both cattle breeds. The results showed that Simmental cattle have a larger, more muscular, and compact body structure with wider chest dimensions, supporting their beef production capacity. Meanwhile, Friesian Holstein cattle tend to have a taller and more elongated body shape, well-developed udder, and physical characteristics that support milk production. The differences in morphological characters between the two cattle breeds are influenced by their production purposes and different management practices. This study indicates notable morphological differences between beef and dairy cattle based on head shape and body size, so that these findings can serve as scientific information and a reference for livestock development according to beef or milk production goals.